Virulence of the Pseudomonas fluorescens clinical strain MFN1032 towards Dictyostelium discoideum and macrophages in relation with type III secretion system - Sperandio, Daniel (BioMed Central, 2012)
BACKGROUND: Pseudomonas fluorescens biovar I MFN1032 is a clinical isolate able to grow at 37°C. This strain displays secretion-mediated hemolytic activity involving phospholipase C and cyclolipopeptides, and a cell-associated hemolytic activity distinct from the secreted hemolytic activity. Cell-associated hemolysis is independent of biosurfactant production and remains in a gacA mutant. Disruption of the hrpU-like operon (the basal part of type III secretion system from rhizospheric strains) suppresses this activity. We hypothesized that this phenotype could reflect evolution of an ancestral mechanism involved in the survival of this species in its natural niche. In this study, we evaluated the hrpU-like operon’s contribution to other virulence mechanisms using a panel of Pseudomonas strains from various sources. RESULTS: We found that MFN1032 inhibited the growth of the amoebae Dictyostelium discoideum and that this inhibition involved the hrpU-like operon and was absent in a gacA mutant. MFN1032 was capable of causing macrophage lysis, if the hrpU-like operon was intact, and this cytotoxicity remained in a gacA mutant. Cell-associated hemolytic activity and macrophage necrosis were found in other P. fluorescens clinical isolates, but not in biocontrol P. fluorescens strains harbouring hrpU-like operon. The growth of Dictyostelium discoideum was inhibited to a different extent by P. fluorescens strains without correlation between this inhibition and hrpU-like operon sequences. CONCLUSIONS: In P. fluorescens MFN1032, the basal part of type III secretion system plays a role in D. discoideum growth inhibition and macrophage necrosis. The inhibition of D. discoideum growth is dependent on the GacS/GacA system, while cell-associated hemolytic activity and macrophage lysis are not. Virulence against eukaryotic cells based on the hrpU-like operon may be more than just a stochastic evolution of a conserved system dedicated to survival in competition with natural predators such as amoebae. It may also mean that there are some important modifications of other type III secretion system components, which remain unknown. Cell-associated hemolysis might be a good indicator of the virulence of Pseudomonas fluorescens strain.